Antibacterial Activity Against Oral Pathogens and Anti–Oral Cancer Activity of Artemisia Species In Vitro. Issue 2 (2nd April 2016) - Lee, Je-Hyuk
ABSTRACT: The antimicrobial activities of Artemisia species Plant extracts against oral pathogens were evaluated by agar-well diffusion assay, while its cytotoxicity on human oral carcinoma cell lines was determined by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide ( MTT) assay . Streptococcus mutans was the most susceptible to A. selengensis and A. keiskeana with 6.0 and 5.0 mm diameters and was superior to the standard drugs, streptomycin and cetylpridinium chloride (CPC) . A. japonica, A. keiskeana, and A. selengensis were susceptible to all tested oral pathogens; A. capillaries and A. sylvatica suppressed the growth of S. mutans, S. sobrinus, and S. epidermidis. A. selengensis had the most control of all oral pathogens, showing the strongest cytotoxicity against oral gingival carcinoma cell . Artemisia sp. showed mild cytotoxicity against oral squamous carcinoma cell. The cytotoxicity against the oral tongue carcinoma cell was observed in all tested Artemisia sp. except for A. sylvatica. Taken together, A. keiskeana and A. selengensis suppressed the growth of the tested bacteria and was cytotoxic to human oral carcinoma cell lines .